2016
DOI: 10.1021/acs.orglett.6b00967
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Copper-Mediated Domino Three-Component Approach to 2-Aminobenzothiazole Derivatives

Abstract: An unprecedented three-component reaction involving a 2,2'-diaminodiaryl disulfide, copper cyanide, and an electrophile is described. This transformation is based on an oxidative copper-mediated S-cyanation as a key step and involves a cyanation/cyclization/acylation domino sequence enabling a rapid and efficient synthesis of diversely substituted 2-aminobenzothiazole derivatives. Notably, this reaction proceeds via an original mechanism involving an intermolecular migration of the acyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is assumed that ortho-thiocyanation reaction occurs at the first step, followed by the addition of amino group to the thiocyanato group. [22,23] Several control experiments using 1a as an example were performed to gain insight into the mechanism (Scheme 3). No reaction occurred in the absence of NCS, indicating NCS is indispensable for this reaction (Scheme 3, a).…”
Section: Scheme 2 Plausible Pathway For the Synthesis Of Compound 2kmentioning
confidence: 99%
“…It is assumed that ortho-thiocyanation reaction occurs at the first step, followed by the addition of amino group to the thiocyanato group. [22,23] Several control experiments using 1a as an example were performed to gain insight into the mechanism (Scheme 3). No reaction occurred in the absence of NCS, indicating NCS is indispensable for this reaction (Scheme 3, a).…”
Section: Scheme 2 Plausible Pathway For the Synthesis Of Compound 2kmentioning
confidence: 99%
“…The ring-substituted 2-aminobenzothiazoles formed in situ from diaminodiaryl disulfides enter the three-component domino reaction, which includes diacylation of diaminodiaryl disulfide, oxidative S-cyanation by CuCN, cyclization via nucleophilic attack of the thiocyanate carbon atom and, finally, intermolecular acyl group migration to the exocyclic nitrogen atom (Scheme 12) [54]. Acylation of 6-substituted 2-aminobenzothiazoles by polysubstituted benzoic acids containing the uracil moiety affords benzamides 13a-i possessing herbicide activity (Scheme 13) [40].…”
Section: Alkylation and Acylation Reactionsmentioning
confidence: 99%
“…In 2016, Donnard, and Gulea et al reported the synthesis of amino-benzothiazole derivatives using a copper-mediated three-component reaction involving an S-cyanation key step (Scheme 39). In that case, starting from ortho-aminothiophenols (102) or their corresponding diaryldisulfides (103), they performed the cyanation of the sulfur atom by an oxidative coupling due to the use of CuCN [40] to form a thiocyanate (105) that can be subsequently attacked by the nitrogen atom to lead to a benzothiazole intermediate that can intermolecularly transfer its protecting group to reach the targeted heterocycle (104) [41,42].…”
Section: Reactions Involving S-cyanationmentioning
confidence: 99%